Clean development mechanism in China: Regional distribution and prospects - Hong, J.; Guo, Xiumei; Marinova, Dora; Yang, F.; Yu, W. (Elsevier Science, 2013)
Late in 2012, when the first commitment period of the Kyoto Protocol came to an end, it was further extended to December 2020. This was based on the strong realisation that the clean development mechanism (CDM) projects have been playing an important role globally, particularly in promoting clean development in China. Based on a review of international and domestic sources, the paper analyses the progress in the development of CDM projects both globally and in China.China has attracted the lion share of CDM investment in terms of projects located in this country and the global annual certified emission reductions under this mechanism. Due to the relative easiness of implementation, the main area of investment is new and renewable energy. China's fast economic development, open door investment policy, political stability, high educational and technological standards and reliable infrastructure are all encouraging the interest of foreign investors seeking to reduce their domestic carbon footprint. In order to facilitate the location of CDM projects, the Chinese government formulated a series of policies and regulations as well as established national coordinating groups for climate change, CDM Designated National Authorities and projects auditing boards, which are responsible for projects application, auditing and management.There are however large differences in the regional distribution of Chinese CDM projects. Provinces, such as Yunnan, Sichuan, Inner Mongolia, Hunan and Gansu (located in central and western China) are attracting more projects because of their rich hydro and wind resources while there are very few projects in the eastern already developed parts of the country. This trend is consistent with the CDM's main goal to assist less developed regions to achieve a more sustainable development.